Performance of QuantiFERON-TB Gold Plus assays in paediatric tuberculosis: a multicentre PTBNET study. Issue 3 (25th October 2022) - Buonsenso, Danilo; Noguera-Julian, Antoni; Moroni, Rossana; Hernández-Bartolomé, Angel; Fritschi, Nora; Lancella, Laura; Cursi, Laura; Soler-Garcia, Aleix; Krüger, Renate; Feiterna-Sperling, Cornelia; Sali, Michela; Lo Vecchio, Andrea; et al.
Abstract : Rationale: In 2016, a new interferon-gamma release assay (IGRA) was introduced, QuantiFERON-TB Gold Plus (QFT-Plus), claimed to have improved sensitivity in active tuberculosis (TB). Objectives: This study aimed to determine the performance of QFT-Plus, compared with previous generation IGRAs and the tuberculin skin test (TST), in children with TB in Europe. Methods: Multicentre, ambispective cohort study within the Paediatric Tuberculosis Network European Trials Group (ptbnet), a dedicated paediatric TB research network comprising >300 members, capturing TB cases <18 years-of-age diagnosed between January 2009 and December 2019. Measurements and main results: 1001 TB cases from 16 countries were included (mean age (IQR) 5.6 (2.4–12.1) years). QFT-Plus was performed in 358, QFT Gold in-Tube (QFT-GIT) in 600, T-SPOT. TB in 58 and TST in 636 cases. The overall test sensitivities were: QFT-Plus 83.8% (95% CI 80.2% to 87.8%), QFT-GIT 85.5% (95% CI 82.7% to 88.3%), T-SPOT. TB 77.6% (95% CI 66.9% to 88.3%) and TST (cut-off ≥10 mm) 83.3% (95% CI 83.3% to 86.2%). There was a trend for tests to have lower sensitivity in patients with miliary and/or central nervous system (CNS) TB (73.1%, 70.9%, 63.6% and 43.5%, respectively), and in immunocompromised patients (75.0%, 59.6%, 45.5% and 59.1%, respectively). Conclusions: The results indicate that the latest generation IGRA assay, QFT-Plus, does not perform better than previous generation IGRAs or the TST in children with TB disease. Overall, tests performed worse in CNS and miliary TB, and in immunocompromised children. None of the tests evaluated had sufficiently high sensitivity to be used as a rule-out test in children with suspected TB.